«Реінкарнація» національного жанру в «Записках на зап’ястях» Лесі Воронюк - Шахова, Катерина; Shakhova, Kateryna (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті розглянуто жанрову своєрідність «Записок на зап’ястях» Лесі Воронюк, обумовлену оригіналь-ним синтезом жанру записок із поезією в прозі; досліджено поетику назви, образ оповідачки, сюжет. Встановлено основні й специфічні ознаки записок у творі, позначені впливом індивідуально-авторського стилю на формування особливого жанрового коду. The article deals with the Lesya Voronyuk’s “Notes on the wrists” as the original author’s experiment, synthesis of notes and poetry in prose, due of specific genre features of work: firstly, prose form, small content, subjective and emotional expression of depicted, discontinuity and fragmentation of the narrative; secondly, there are specific features of notes (first-person narration, narrator’s type, the autobiographical elements, genre marker in the title etc.) and poetry in prose (feelings, emotions, lyricism, diversity of art tools, replacement plot by motifs). Poetics of the title of “Notes on the wrists” focuses on the story of its creation: the art notes born from spontaneous daily records, which witness the change in outlook, reflect the way of internal search, introspection, author’s expression in the word. The study reveals the images of narrator and the main characters; it observes the key points of plot. Thus the “Notes on the wrists” by Lesya Voronyuk represent the modern individual author’s interpretation of notes and formation of new genre code.
The “Reincarnation” of National Genre in “Notes on the wrists” by Lesya Voronyuk
Keywords: записки; поезія в прозі; оповідач; жанр; стиль; notes; poetry in prose; narrator; genre; style